2005
DOI: 10.1038/sj.npp.1300919
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the 5-Hydroxytryptamine 2A Receptor and CytochromeP4502D6 Genes Synergistically Predict Fluvoxamine-Induced Side Effects in Japanese Depressed Patients

Abstract: 5-Hydroxytryptamine (5-HT) receptors are thought to be associated with the gastrointestinal side effects induced by selective serotonin reuptake inhibitors. CytochromeP450 (CYP) 2D6 may also be associated with the side effects induced by fluvoxamine, since the plasma fluvoxamine concentration depends on a CYP2D6 gene polymorphism. This study investigated whether 5-HT receptor and CYP2D6 gene polymorphisms could predict the occurrence of the side effects. The effects of 5-HT receptor and CYP2D6 gene polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 20 publications
0
34
1
Order By: Relevance
“…For example, the receptor is a well established target in the treatment of nausea and emesis. The association between the 5-HT 3B (Y129S) polymorphism and various forms of nausea and/or emesis (induced by selective serotonin-reuptake inhibitors or chemotherapy) has been investigated with divergent results (21,28,29). Future studies are required to determine the possible contributions of the 5-HT 3B (Y129S) polymorphism to the development and/or the treatment efficacy of the nausea and emesis known to be common side effects of radio/chemotherapy, anesthetics, and antidepressants.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the receptor is a well established target in the treatment of nausea and emesis. The association between the 5-HT 3B (Y129S) polymorphism and various forms of nausea and/or emesis (induced by selective serotonin-reuptake inhibitors or chemotherapy) has been investigated with divergent results (21,28,29). Future studies are required to determine the possible contributions of the 5-HT 3B (Y129S) polymorphism to the development and/or the treatment efficacy of the nausea and emesis known to be common side effects of radio/chemotherapy, anesthetics, and antidepressants.…”
Section: Discussionmentioning
confidence: 99%
“…256 Three variations within the coding region of 5-HT 2A have been implicated in antidepressant response: 102T>C (rs 6313) 176 and 1438G>A (rs6311) 190,257 and 1420C>T, 153 although results were not unequivocal and some findings not replicated. 52,83,85,116,153,185,258 The variants 102T>C and 1438G>A are 2 of the most investigated polymorphisms of this gene: they are in linkage disequilibrium, and they can be considered together. 259 Several other variants have been reported to predict antidepressant response.…”
Section: Serotonin 2amentioning
confidence: 99%
“…264 An association with vomiting and nausea, both caused by chemotherapy and paroxetine, was reported with the -100 -102 AAG deletion variant of HTR3B. 265 Conflicting findings were reported for the HTR3A 195C>T (rs62625041) and 178C>T SNPs with respect to the gastrointestinal side effects induced by SSRIs, 52,190,266 whereas the HTR3B polymorphism at position 129 leading to a tyrosine-to-serine substitution (rs1176744) was found to be associated with nausea induced by paroxetine, 266 but conflicting findings have been reported.…”
Section: Serotonin 3a and 3bmentioning
confidence: 99%
“…Although the number of association studies involving the serotonin system increased annually between 1995 and 2005 (from 14 per annum in 1995, to 150 in 2005 [ Figure 3]), only four studies [45][46][47][48] of a total of 875 reported over the preceding decade evaluated serotonin system-related genes together with genes involved in pharmacokinetics (Table 1). Notably, the established or putative endogenous substrates of respective pharmacokinetic genes were not mentioned or discussed in any of these studies.…”
Section: Figure 1 the Pharmacological Cascade Of Biological Events Smentioning
confidence: 99%